Atopic Dermatitis in America Study: A Cross-Sectional Study Examining the Prevalence and Disease Burden of Atopic Dermatitis in the US Adult Population - Chiesa Fuxench, Zelma C; Block, Julie K; Boguniewicz, Mark; Boyle, John; Fonacier, Luz; Gelfand, Joel M; Grayson, Mitchell H; Margolis, David J; Mitchell, Lynda; Silverberg, Jonathan I; Schwartz, Lawrence; Simpson, Eric L; et al. (Journal of investigative dermatology, 2019)
Population-based estimates on the prevalence of atopic dermatitis in adults vary widely. The objectives of this study were to determine the prevalence of atopic dermatitis in the population of the United States, the distribution of disease severity, and its impact on health-related quality of life. Among 1,278 participating adults, the prevalence (95% confidence interval) of atopic dermatitis was 7.3% (5.9-8.8). Overall, 60.1% (56.1-64.1) of participants were classified as having mild, 28.9% (25.3-32.7) as having moderate, and 11% as having severe (8.6-13.7) disease. Patients with atopic dermatitis and those with more severe disease had higher scores in the dermatology life quality index (mean [standard deviation] for AD patients = 4.71 [6.44] vs. control individuals = 0.97 [2.12]) (P < 0.001) and the hospital anxiety (mean [standard deviation] for AD patients = 7.03 [4.80] vs. control individuals = 4.73 [4.8]) and depression (mean, [standard deviation] for AD patients = 5.83 [4.54] vs. control individuals = 3.62 [3.61]) scales, indicating a worse impact on quality of life and an increased likelihood of anxiety or depression. Based on our prevalence estimates, 16.5 million adults would have a diagnosis of atopic dermatitis, with 6.6 million meeting criteria for moderate to severe disease. Our study confirms the high prevalence and disease burden of atopic dermatitis in this population.